Genome-wide identification and expression analysis of the PIN gene family in the pepper pedicel abscission zone and during root development - HE Lei; YAN Xi; LAI Wei; LIU Chongzheng; YANG Hong; HE Jianwen (Xibei zhiwu xuebao)
[Objective] This study seeks to identify and analyze the PIN gene family members in pepper (Capsicum annuum L.) and to investigate their expression patterns in the abscission zone of the fruit pedicel as well as during root development. The ultimate goal is to provide candidate genes for elucidating the function of CaPINs and for breeding new pepper varieties. [Methods] PIN genes were identified through whole-genome screening of pepper, followed by comprehensive bioinformatics analysis. The expression patterns of these genes in the fruit pedicel abscission zone and during root development were systematically analyzed. [Results] 9 members of the PIN gene family were identified in the pepper genome and designated as CaPIN1 through CaPIN9. These genes are distributed across seven chromosomes, with CaPIN9 remaining unanchored. The proteins encoded by these genes exhibit amino acid length ranging from 358 to 654 residues, molecular weight from 39 251.05 D to 71 170.91 D, and isoelectric point from 6.40 to 9.38. Most of these proteins are stable. Additionally, significant collinearity was observed among the CaPINs, indicating a close genetic relationship with the tomato genome. CaPINs encompass a multitude of elements associated with growth, environmental responses, and hormonal signaling. Transcriptome data analysis revealed that the expression of CaPINs in pepper was tissue-specific. Quantitative PCR results demonstrated that CaPINs exhibited differential expression levels across various fruit pedicel abscission zones and throughout root development. [Conclusion] CaPINs play a crucial role in the development of the pedicel abscission zone and the growth and development of the root system. These genes hold significant potential as candidates for breeding pepper varieties with improved ease of de-stemming and for enhancing genetic traits related to root systems.